Integration of Social Media in Christian Religious Education: Its Impact on Student–Lecturer Interaction - Ronsumbre, Tirza; Rasinus, Rasinus; Rukua', Ivo Sastri; Karlau, Sensius Amon; Payage, Neri (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2025)
This study examines the integration of social media in Christian Education and its impact on the interaction between students and lecturers. With the development of digital technology, the use of social media in education has become increasingly relevant to enhance student engagement and facilitate communication in learning. The study adopts a quantitative approach using a survey method, collecting data through questionnaires distributed to students and lecturers involved in Christian Education that incorporates social media. The findings show that the integration of social media positively influences the interaction between students and lecturers, offering benefits in enhancing collaboration, accessibility to materials, and student participation. However, the study also identifies challenges related to content accuracy and professionalism in using social media. This research is expected to contribute to the development of more effective and relevant Christian Education teaching methods in the digital era.